Strengthening Biosecurity in Iraq: Development of a National Biorisk Management System - Al Jewari, Mahdi F. H.; Koblentz, Gregory D. (Frontiers in Public Health, 2016)
Since 2004, the Republic of Iraq has undertaken a concerted effort to comply with all of its international obligations to prevent the proliferation and the use of chemical, biological, radiological, and nuclear (CBRN) weapons. A centerpiece of this effort is Iraq’s development of a National Biorisk Management System. The Iraqi National Monitoring Authority (INMA), which is responsible for CBRN security and non-proliferation in Iraq, has played a key role in establishing this system. This article provides an overview of Iraq’s international non-proliferation commitments, describes the legal and organizational steps it has taken to implement these commitments, and examines current initiatives to strengthen Iraq’s biosecurity.